2015
DOI: 10.1155/2015/796762
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Needleless Connector Hubs: Clinical Evidence Systematic Review

Abstract: Background. Needleless connectors (NC) are used on virtually all intravascular devices, providing an easy access point for infusion connection. Colonization of NC is considered the cause of 50% of postinsertion catheter-related infections. Breaks in aseptic technique, from failure to disinfect, result in contamination and subsequent biofilm formation within NC and catheters increasing the potential for infection of central and peripheral catheters. Methods. This systematic review evaluated 140 studies and 34 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 151 publications
0
37
0
11
Order By: Relevance
“…Among the implications for the practice of neonatal nurse are the initial and continuing education of professionals who insert and handle catheters daily, the adoption of aseptic technique and maximum precautions, the use of ultrasound guided venipuncture for catheter insertion, the use of transparent bioclusive dressings for protection of the catheter insertion site , disinfecting all access ports of the catheter with proper antiseptic prior to use, the use of needleless catheter connectors, as the colonization of these connectors is considered to be the cause of 50% of the post-insertion catheter-related infections which occur when there is a technical failure of disinfection, resulting in contamination and formation of a biofilm inside the connectors. (13,(18)(19)(20) The evidence about the benefits of teams with a limited number of highly trained professionals caring for the PICCs is evidenced. Other recommendations for preventing complications in newborns include: early identification of candidates for catheter insertion, preservation of the antecubital fossa for possible insertions, detailed information on the types of catheter available in the health service, indicating the type of catheter according to the prescribed intravenous therapy and the clinical condition of neonates, and the clinical management of complications based on evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Among the implications for the practice of neonatal nurse are the initial and continuing education of professionals who insert and handle catheters daily, the adoption of aseptic technique and maximum precautions, the use of ultrasound guided venipuncture for catheter insertion, the use of transparent bioclusive dressings for protection of the catheter insertion site , disinfecting all access ports of the catheter with proper antiseptic prior to use, the use of needleless catheter connectors, as the colonization of these connectors is considered to be the cause of 50% of the post-insertion catheter-related infections which occur when there is a technical failure of disinfection, resulting in contamination and formation of a biofilm inside the connectors. (13,(18)(19)(20) The evidence about the benefits of teams with a limited number of highly trained professionals caring for the PICCs is evidenced. Other recommendations for preventing complications in newborns include: early identification of candidates for catheter insertion, preservation of the antecubital fossa for possible insertions, detailed information on the types of catheter available in the health service, indicating the type of catheter according to the prescribed intravenous therapy and the clinical condition of neonates, and the clinical management of complications based on evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The child’s case study, in agreement with previous literature,2 3 has demonstrated that the harm associated with CVADs frequently occurs during the later stages of CVAD dwell, not on the early days after insertion. Paediatric CVAD maintenance procedures such as flushing,20 dressing,21 administration set changes,22 and hub decontamination23 are not well supported by evidence, likely perpetuating these preventable complications for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, mencionan que los tapones con clorhexidina alcohólica también son efectivos en la prevención de la contaminación y la completa desinfección de la superficie de los CSA; no obstante, su efecto aún no ha sido tan ampliamente estudiado, debido a que no se encuentran disponibles comercialmente en diversos países 18 .…”
Section: ¿Cuál Es El Agente Desinfectante De Uso Más Común En La Desiunclassified